Sucrose content in latex of native rubber trees stimulated with ethrel - Moraes, Vicente H.F.; R. Neto, Olinto G. da; Seeschaaf, Karl Wilhelm (Pesquisa Agropecuaria Brasileira, 2014)
A survey of the physiological state of wild rubber trees was performed through the determination of sucrose concentration in latex to ascertain whether yield stimulation with Ethrel would be a risk of inducing dryness. The high levels of sucrose content in latex just after the annual six-month period of exploitation and the even higher contents after a five-month rest period convincingly deny any possibility of tree exhaustion, when tapping is done under the correct stimulation procedure. This should in fact be expected, due to the low tapping intensity of wild rubber trees as compared to the cultivated ones.